2021
DOI: 10.1101/2021.03.19.21253973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MRSD: a novel quantitative approach for assessing suitability of RNA-seq in the clinical investigation of mis-splicing in Mendelian disease

Abstract: BackgroundRNA-sequencing of patient biosamples is a promising approach to delineate the impact of genomic variants on splicing, but variable gene expression between tissues complicates selection of appropriate tissues. Relative expression level is often used as a metric to predict RNA-sequencing utility. Here, we describe a gene- and tissue-specific metric to inform the feasibility of RNA-sequencing, overcoming some issues with using expression values alone.ResultsWe derive a novel metric, Minimum Required Seq… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Strong weighting of PS3 for identified aberrant splicing should only be used when (1) expression profiles in the biosample used match those of the primary disease tissue of the candidate genes [ 62 ], and (2) the sequencing data generated is appropriate for the detection of aberrant splicing events (e.g. exceeds the 95% confidence interval recommendations from MRSD (minimum required sequencing depth) using appropriate parameters for the laboratory and bioinformatics approaches applied [ 63 ]). In addition, we recommend that BS3 is only used in the absence of aberrant splicing events when there is evidence that both alleles are being expressed (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Strong weighting of PS3 for identified aberrant splicing should only be used when (1) expression profiles in the biosample used match those of the primary disease tissue of the candidate genes [ 62 ], and (2) the sequencing data generated is appropriate for the detection of aberrant splicing events (e.g. exceeds the 95% confidence interval recommendations from MRSD (minimum required sequencing depth) using appropriate parameters for the laboratory and bioinformatics approaches applied [ 63 ]). In addition, we recommend that BS3 is only used in the absence of aberrant splicing events when there is evidence that both alleles are being expressed (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Minimum Required Sequencing Depth (MRSD) informs biosample selection (whole blood, lymphoblastic cell lines, and skeletal muscle) by estimating the minimum sequencing depth required from RNA-sequencing to achieve desired coverage across a given gene or gene panel. The authors reported high precision, and their results suggest that lymphoblastic cell lines may be suitable for ∼70% of established disease gene panels (Rowlands et al, 2021).…”
Section: Integrating Multi-omics Datamentioning
confidence: 95%
“…A study targeting genes well expressed in the chosen tissue will need fewer sequencing reads to survey splicing than a study with genes that are poorly expressed. A recent preprint by Rowlands et al presents a web tool 2 that can be used to calculate the minimum required sequencing depth to profile splicing based on the level of expression of genes of interest in three different CATs, which will assist in choosing the appropriate sequencing depth (and target tissue type) in study design ( Rowlands et al, 2021b ). An additional consideration here is that disruption to splicing often leads disruption of the transcript’s open reading frame and the introduction of a premature termination codon.…”
Section: Classification Of Potentially Splice Disrupting Variantsmentioning
confidence: 99%